Introduction: The Politics of Gender and Agriculture - Njuki, J.; Tufan, H.A.; Polar, Vivian; Campos, Hugo; Morgan-Bell, M.; Wilde, V. (2024)
As researchers and practitioners at various stages of our careers and from diverse disciplines, with many decades of collective experience, we have witnessed an evolution in the theory and practice of gender and agriculture. What compelled us to put this book together was a growing sense of frustration from the global community of gender and agriculture researchers with the pervasive co-option of the “gender agenda”, along with a de-politization of its critical theories and interventions with roots in radical change. We recognize this book is a synopsis of only some possible perspectives, but in reaching out to authors to contribute, it was our aim to create an opportunity to publish the things they felt are urgent today, but perhaps felt were too disruptive, challenging or without enough space in the mainstream body of literature. In what follows, we question some of the assumptions that underpin agricultural research and development, make clear our support for the nascent rise of more feminist and rights-based development models, and set the scene for this book. We call for a reset.